Bilateral Aberrant Internal Carotid Arteries with Bilateral Persistent Stapedial Arteries and Bilateral Duplicated Internal Carotid Arteries - Roll, John D.; Urban, Martin A.; Larson, Theodore C.; Gailloud, Philippe; Jacob, Pradeep; Harnsberger, H. Ric (American Journal of Neuroradiology, 2003)
Summary: A 5-year-old boy was evaluated for a left retrotympanic mass found at otoscopy. Subsequent petrous bone CT and MR angiographic examinations demonstrated bilateral aberrant internal carotid, bilateral stapedial artery persistence, and bilateral duplicated internal carotid arteries. Imaging findings and their clinical relevance are discussed. A second case of unilateral aberrant internal carotid artery with a persistent stapedial artery is included for comparison.